EMPOWERMENT OF LEATHER BAG CRAFTSMEN MSMES IN TANGGULANGIN BASED ON DIGITAL MARKETING - Alfarizi, Mochamat Royfen Cahya; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the empowerment of Micro, Small, and Medium Enterprises (MSMEs) leather bag craftsmen in Kludan Village through the implementation of Digital Marketing strategies. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. Results: The findings reveal that the Kludan Village government has provided structured training and mentoring programs on Digital Marketing to enhance the online marketing capacity of MSMEs and broaden their market reach. Despite these efforts, MSMEs face challenges such as low digital literacy and limited access to technology, particularly among elderly entrepreneurs. To address these barriers, the government has offered continuous mentoring, equipment support, and facilitated the creation of Business Identification Numbers (NIB). Novelty: This study highlights Digital Marketing as a strategic and sustainable solution for strengthening local economies in rural areas, emphasizing the critical role of government-led interventions in bridging the digital divide and enabling MSMEs to adapt effectively to the demands of the digital era.